2020
DOI: 10.1371/journal.pone.0234492
|View full text |Cite
|
Sign up to set email alerts
|

The soluble VEGF receptor sFlt-1 contributes to endothelial dysfunction in IgA nephropathy

Abstract: Endothelial injury is a common manifestation in IgA nephropathy (IgAN). After the previous identification of the upregulated soluble fms-like tyrosine kinase-1 (sFlt-1) correlated with endothelial injury in IgAN, in the present study, we further explored the role of sFlt-1 in endothelial injury in IgAN. We enrolled 72 patients with IgAN and detected the sFlt-1 levels. The polymeric IgA1 (pIgA1) complexes were isolated from the pooled plasma samples of another 10 patients with IgAN. Apoptosis proteins were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Irreparable mitochondrial damage will release pro-apoptotic proteins into the cytoplasm and initiate the mitochondria-mediated death pathway. Endothelial mitochondrial dysfunction has been linked to several diseases such as diabetes-induced microvascular injury, cerebral ischemia-reperfusion injury ( Zhang et al, 2020 ), nephropathy ( Zhai et al, 2020 ), peripheral artery disease ( Park et al, 2020 ), and pulmonary artery hypertension ( Wang et al, 2020 ). Many researches have observed the role of mitochondrial damage in triggering endothelial dysfunction upon ox-LDL treatment ( Li et al, 2018 , Li et al, 2020 ; Yuan et al, 2019 ; Xie et al, 2020 ), suggesting an urgent need for therapies that protect endothelial mitochondria in order to reduce atherosclerosis development.…”
Section: Introductionmentioning
confidence: 99%
“…Irreparable mitochondrial damage will release pro-apoptotic proteins into the cytoplasm and initiate the mitochondria-mediated death pathway. Endothelial mitochondrial dysfunction has been linked to several diseases such as diabetes-induced microvascular injury, cerebral ischemia-reperfusion injury ( Zhang et al, 2020 ), nephropathy ( Zhai et al, 2020 ), peripheral artery disease ( Park et al, 2020 ), and pulmonary artery hypertension ( Wang et al, 2020 ). Many researches have observed the role of mitochondrial damage in triggering endothelial dysfunction upon ox-LDL treatment ( Li et al, 2018 , Li et al, 2020 ; Yuan et al, 2019 ; Xie et al, 2020 ), suggesting an urgent need for therapies that protect endothelial mitochondria in order to reduce atherosclerosis development.…”
Section: Introductionmentioning
confidence: 99%
“…[ 43 ]. Zhai et al showed that the proliferation of HUVECs was damaged and apoptosis was up-regulated when stimulated by sFlt-1, which further demonstrates that sFlt-1 contributes to endothelial dysfunction [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TwHF extracts contained novel inhibitors of MMP including MMP9 thus might have therapeutic potential in arthritis and other conditions associated with increased MMPs like IgAN ( 38 , 39 ). CASP3 is known as a representative effector of apoptosis, cleaved caspase-3 active fragment could mediate apoptosis in endothelial cells ( 40 ). PTGS2 also known as cyclooxygenase 2 (COX2), is the key enzyme in prostaglandin biosynthesis, and is responsible for the prostanoid biosynthesis involved in inflammation and mitogenesis.…”
Section: Discussionmentioning
confidence: 99%